2020
DOI: 10.2147/dddt.s242521
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hydrogen Sulfide Protects Against High Glucose-Induced Human Umbilical Vein Endothelial Cell Injury Through Activating PI3K/Akt/eNOS Pathway</p>

Abstract: Dysfunction of endothelial cells plays a key role in the pathogenesis of diabetic atherosclerosis. High glucose (HG) has been found as a key factor in the progression of diabetic complications, including atherosclerosis. PI3K/Akt/eNOS signaling pathway has been shown to involve in HG-induced vascular injuries. Hydrogen sulfide (H 2 S) has been found to exhibit protective effects on HG-induced vascular injuries. Moreover, H 2 S activates PI3K/Akt/eNOS pathway in endothelial cells. Thus, the present study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 67 publications
1
47
0
4
Order By: Relevance
“…It has been suggested that activation of AKT and ERK 1/2 pathways are able to optimize cellular functions and promote endothelial cell survival and tube formation (38,56). HG damages endothelial cell function by inhibiting AKT and ERK 1/2 pathways (57,58). DM down-regulates the activation of AKT and ERK 1/2, resulting in delayed wound healing by decreasing proliferation and increasing cellular apoptosis (59), whereas activation of AKT and ERK 1/2 accelerates not only corneal wound healing but also cutaneous wound closure (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that activation of AKT and ERK 1/2 pathways are able to optimize cellular functions and promote endothelial cell survival and tube formation (38,56). HG damages endothelial cell function by inhibiting AKT and ERK 1/2 pathways (57,58). DM down-regulates the activation of AKT and ERK 1/2, resulting in delayed wound healing by decreasing proliferation and increasing cellular apoptosis (59), whereas activation of AKT and ERK 1/2 accelerates not only corneal wound healing but also cutaneous wound closure (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The physiological concentration of NO produced by eNOS has anti-apoptotic and cytoprotective effects [39,40]. Andrographolide, hydrogen sulfide, and oxymatrine were reported to inhibit endothelial cell apoptosis through upregulating Akt/eNOS pathway [41][42][43]. Moreover, eNOS deficiency increased endothelial cell apoptosis and aggravated renal injury in mice with remnant kidney [44].…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of TCM and its components on endothelial cells is well recognized [ 41 43 ]. Most studies demonstrated the involvement of the PI3K-AKT signaling pathway, among which the expression of eNOs is regulated affecting the NO levels [ 44 46 ]. This signaling molecule acts widely in the body involved vasodilation and circulation, regulation of inflammation, and platelet activity, while ET has a strong vasoconstrictor effect.…”
Section: Discussionmentioning
confidence: 99%